Assessment of comorbidities and COVID-19 pneumonia prognosis: a literature review - Llanos Tejada, Félix K. (2021)
Mortality due to SARS-CoV-2 is high compared to that caused by other respiratory viruses. This article aims to define the comorbidities associated with high mortality rates or complications that require ventilatory support in intensive care units. A bibliographic search has been performed with respect to comorbidities and/or alterations in laboratory tests and radiographic exams that have been associated with mortality, especially those described in China.